2021
DOI: 10.1002/nop2.902
|View full text |Cite
|
Sign up to set email alerts
|

Influence of psychological stress and coping styles in the professional identity of undergraduate nursing students after the outbreak of COVID‐19: A cross‐sectional study in China

Abstract: Aim To investigate the influencing factors in professional identity of undergraduate nursing students after the outbreak of COVID‐19. Design Cross‐sectional study. Methods The study covered 2,999 nursing students in six undergraduate nursing schools. Several self‐report questionnaires were used to collect the general information, psychological stress, coping styles and professional identity of the undergraduate nursing students. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
1
15
0
1
Order By: Relevance
“…In the evaluation eligibility stage, out of 225 remaining articles, 210 ineligible articles were removed following the examination of their full text, and similarly according to the inclusion and exclusion criteria. In the quality evaluation stage, by reading the full text of the article and based on the score obtained from AHRQ checklist, 15 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] articles were entered into the final analysis (Fig. 2).…”
Section: Literature Screening Process and Resultsmentioning
confidence: 99%
“…In the evaluation eligibility stage, out of 225 remaining articles, 210 ineligible articles were removed following the examination of their full text, and similarly according to the inclusion and exclusion criteria. In the quality evaluation stage, by reading the full text of the article and based on the score obtained from AHRQ checklist, 15 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] articles were entered into the final analysis (Fig. 2).…”
Section: Literature Screening Process and Resultsmentioning
confidence: 99%
“…Professional identity among medical students refers to their acceptance and recognition of their chosen major and their willingness to devote themselves to learning with a positive attitude and positive behavior [ 19 ]. Medical college is where medical students are likely to experience professional medicine for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of psychological stress among recruits in the U.S. Army is 28.2%, 33.1% among recruits in the Brazilian Army, and 31.5% in Chinese Army (Jackson et al, 2011). Studies have shown that individuals in a state of psychological stress influence the choice of coping styles and action strategies, and there is a significant correlation between psychological stress and coping styles (Liu et al, 2020;Zhao et al, 2021). Coping styles are the emotional and behavioral styles that individuals exhibit in response to various dilemmas (Zhao, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The currently recognized factors that influence the coping style are attributed to individual factors and external factors. Individual factors refer to age (Stevenson et al, 2012), personal alexithymia (Shen and Xing, 2020), personality (Jurczak et al, 2019), psychological stress (Zhao et al, 2021), etc. External factors include stress (Ryu et al, 2020), social support (Yu et al, 2020), and family environment (Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%